The Digital Divide Vs. The E-Government Divide: Do Socio-Demographic Variables (Still) Impact E-Government Use Among Onliners? - Niehaves, Björn; Gorbacheva, Elena; Plattfaut, Ralf (20th European Conference on Information Systems (ECIS), 2012)
E-Government brings mutual benefits to both citizens and public administrations. However, there exists a gap between adopters and non-adopters of e-Government services. Most studies in this field explore e-Government acceptance on the basis of the entire population, while investigation of onliners rarely takes place. Against the background that the number of internet users is increasing steadily, we identify the need to differentiate general internet adoption (digital divide) effects and e-Government-specific divide effects. In our study, we thus develop a research framework, where the cumulative effect of e-Government adoption (among all people) is split into a) the digital divide effect and b) the e-Government divide effect (among internet users). We derive three corresponding research models and examine the influence of socio-demographic factors: age, gender, income, and education. We test our research framework using comprehensive survey data (n = 1930). Analysis of our results justifies the separation of the e-Government divide effect from the cumulative effect of e-Government adoption, because the factors influencing e-Government usage among the entire population and among onliners are proved to be different. Implications for theory and recommendations for practice are discussed.
Keywords: Digital Divide; e-Government; Quantitative Study; Technology Acceptance